Use of 68Ga-PSMA-11 and 18F-FDG PET-CT Dual-Tracer to Differentiate Between Lymph Node Metastases and Ganglia - Shi, Yiping; Xu, Lian; Zhu, Yinjie; Wang, Yining; Chen, Ruohua; Liu, Jianjun (Frontiers in Oncology, 2021)
Purpose Differentiating lymph node metastases (LNM) from peripheral ganglia by physiological prostate-specific membrane antigen (PSMA) uptake is challenging. Two tracers (68Ga-PSMA-11 and 18F-fluorodeoxyglucose [FDG]) metabolic uptake patterns were evaluated by positron emission tomography-computed tomography (PET-CT), searching for differences that could tell ganglia from LNM. Methods Dual 68Ga-PSMA-11 and 18F-FDG PET-CT data of 138 prostate cancer patients acquired from June 2018 to December 2019 were retrospectively evaluated. Ganglia and LNM with PSMA-11 uptake above local background were analyzed by the location and PSMA-11-PET and FDG-PET maximum standardized uptake value (SUVmax). Results PSMA-11-positive ganglia (n = 381) and LNM (n = 83) were identified in 138 and 58 patients, respectively. The LNM SUVmax of PSMA-11-PET (16.4 ± 14.8 vs 2.3 ± 0.7, P < 0.001) and FDG-PET (3.3 ± 3.2 vs 1.5 ± 0.5, P < 0.001) were higher than in ganglia. The probabilities of being an LNM in the low-potential (PSMA-11-PET SUVmax of <4.1 and FDG-PET SUVmax of <2.05), moderate-potential (PSMA-11-PET SUVmax of >4.1 and FDG-PET SUVmax of <2.05, or PSMA-11-PET SUVmax of <4.1 and FDG-PET SUVmax of >2.05), and high-potential (PSMA-11-PET SUVmax of >4.1 and FDG-PET SUVmax of >2.05) groups were 0.9% (3/334), 44.6% (37/83), and 91.5% (43/47), respectively (P < 0.001). The cervical and coeliac ganglia had higher PSMA-11 and FDG uptake than the sacral ganglia (P < 0.001 for all). LNM PSMA-11 and FDG uptake was similar in these three locations. Conclusion The FDG-PET and PSMA-11-PET SUVmax, especially when combined, could well differentiate LNM from ganglia. The tracers uptake differed between cervical/coeliac and sacral ganglia, so the lesion location should be considered during image assessment.